From Understanding to Action: Exploring Sned Teachers in Implementing a School-Based Guidance Program - Zosie Joy G. Ruedas; Felinita III R. Doronio (Future Science / FSH-PH Publications, 2026)
As inclusive education continues to develop, there remains limited research and awareness on how schools address the guidance needs of learners with disabilities. Using a qualitative phenomenological design, this study explored the lived experiences of 10 Special Needs Education (SNED) teachers of Magugpo Pilot Imelda Elementary School – SPED Center in implementing a school-based guidance program for learners with special needs. The researcher conducted in-depth interviews with SNED teachers to understand their experiences and challenges. The findings showed that the overall experiences of Special Needs Education (SNED) teachers in implementation of guidance programs involve taking on multiple roles, which SNED teachers find challenging and very tiring. The findings also revealed that the positive aspects of implementation include seeing learners make progress, seeing learners from self-contained to mainstream, and gain confidence. On the other hand, the challenges include a lack of trainings and expertise of teachers, limited resources, and teachers not being open to student. Additionally, at times, no guidance counselor available, or teachers sometimes work alone, which presents another challenge. The findings also highlighted ways to manage or address the challenges are through collaboration with stakeholders and parents, through resourcefulness, through exchange learning and through seeking peer support. Moreover, some regular teachers were not fully open to inclusive education practices. This study highlighted the need for professional development, sufficient resources, and stronger collaboration among teachers, administrators, and guidance personnel to ensure the effective delivery of guidance services for learners with special needs.